(2x-4)/(x+5)=-3

Simple and best practice solution for (2x-4)/(x+5)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-4)/(x+5)=-3 equation:


D( x )

x+5 = 0

x+5 = 0

x+5 = 0

x+5 = 0 // - 5

x = -5

x in (-oo:-5) U (-5:+oo)

(2*x-4)/(x+5) = -3 // + 3

(2*x-4)/(x+5)+3 = 0

(2*x-4)/(x+5)+(3*(x+5))/(x+5) = 0

3*(x+5)+2*x-4 = 0

5*x+11 = 0

(5*x+11)/(x+5) = 0

(5*x+11)/(x+5) = 0 // * x+5

5*x+11 = 0

5*x+11 = 0 // - 11

5*x = -11 // : 5

x = -11/5

x = -11/5

See similar equations:

| -11-4=-9/4n | | (2x-4)/(x+5)=1 | | -20-(-46)=x/12 | | (x+2)/(3-x)=3 | | 15d=300 | | 8/3m=-9+7 | | -x+9y=-13 | | 7(3x-6)=24 | | 6(x)-8(y)=3 | | 6(-2)-8(-3)=3 | | 8-8y=-16 | | 4/5x=3/10 | | (8x-3)=(x+5) | | 8-4x=-6x | | 1/3n=2/3 | | 1.25+3.69/0.3=47.9 | | 5n+12=27 | | 20+x=-5 | | 4x^2-9x-60=0 | | 7=x-.2 | | -30+x=-17 | | (1+y)(5y-8)=0 | | 5x+44=9x+2 | | 194-5x=40x+19 | | x+.3=5 | | 13-8x=70-29x | | 5/6s+3/4=11/12 | | t/6+3=8 | | 9x+1=26 | | 37+12m=85 | | -44=-3m-2 | | 3x+2g= |

Equations solver categories